Mitigation of Voltage Sag Caused by Single Line to Ground Fault in Distribution System by using Dynamic Voltage Restorer in Matlab/Simulink - Mohamad Rosli, Muhammad Afiq; Muhammad Soomro, Dur (Evolution in Electrical and Electronic Engineering, 2021)
Power quality (PQ) has been concern for electrical engineers since last two decades. Distribution system has always been exposed to many type of disturbances. Review shows that about 70% of the faults in power system are of single line to ground fault (SLGF). The major problem that occur in distribution system is voltage sag cause by SLGF. One way to solve the problem is by using power custom devices like dynamic voltage restorer (DVR). In this project, distribution feeder system has been developed with three cases which are steady-state case, SLGF case and mitigation of SLGF cause. The DVR was designed and applied to mitigate the cause. The aim for the project is to mitigate voltage sag based on institute of electrical and electronics engineer (IEEE) standard 1159. The system was developed in MATLAB/Simulink (2018a). The result show that the DVR for compensating voltage sag caused by SLGF is successfully and the performance DVR against voltage sag.